A Case of Multiple Perineuriomas in the Colon With Underlying Neurofibromatosis Type I. Issue 9 (4th September 2021) - Tsuchiya, Tomoaki; Iwaya, Yugo; Iwaya, Mai; Okamura, Takuma; Nagaya, Tadanobu; Umemura, Takeji
ABSTRACT: A 45-year-old woman was referred to us after a positive fecal occult blood test. Colonoscopy revealed a 20-mm polyp in the transverse colon and a 10-mm polyp in the sigmoid colon. Endoscopic mucosal resection was performed as a diagnostic treatment. Both resected polyps were histologically diagnosed as perineuriomas. She was later found to exhibit multiple café-au-lait spots on the skin and subsequently diagnosed as having neurofibromatosis type I (NF-1). Perineuriomas are rare benign peripheral nerve sheath tumors, with no reports of multiple colonic lesions in a patient with NF-1 to date. NF-1 might be associated with the onset of multiple perineuriomas.